The Correlation Utilization Of Learning Facilities and Learning Independence With Mathematics Learning Outcome Of Grade VIII Students In Islamic Junior School - Pancarita; Desti haryani (JURNAL PENDIDIKAN, 2020)
This research aimed to determine: 1) coefficient Correlation betweenthe utilization of learning facilities with mathematics learning outcome. 2)coefficient correlation between independence learning with mathematics learning outcome. 3) coefficient correlation utilization of learning facilitiesand learning independence with mathematics learning outcome.The research was conducted in the even semester of 2019. The samplein this research was selected from the whole population of students ofGrade VIII in An Nur Islamic Junior School Palangka Raya in 2018/2019Academic Year, in total 78 students. Type of this research is correlational.Two instruments used in this research were questionnaires and tests.Questionnaires of utilization of learning facilities consists of 24 validstatements with 0,78 reliability coefficient, questionnaires of independencelearning consists of 24 valid statements with 0,90 reliability coefficient, andthe mathematics learning outcome test consists of 25 valid items with areliability coefficient of 0.85.The research results concluded: 1) there is positive correlation thatsignificant between utilization of learning facilities with mathematicslearning outcome (rhit=0,58), 2) there is positive correlation that significantbetween independence learning with mathematics learning outcome(rhit=0,54), 3) there is positive correlation that significant betweenutilization of learning facilities and independence learning withmathematics learning outcome (Rhit=0,73), each at a significance level of5%.